2017
DOI: 10.1074/jbc.m116.770149
|View full text |Cite
|
Sign up to set email alerts
|

A mammalian homolog of the zebrafish transmembrane protein 2 (TMEM2) is the long-sought-after cell-surface hyaluronidase

Abstract: Edited by Amanda J. Fosang Hyaluronan (HA) is an extremely large polysaccharide (glycosaminoglycan) involved in many cellular functions. HA catabolism is thought to involve the initial cleavage of extracellular high-molecular-weight (HMW) HA into intermediate-size HA by an extracellular or cell-surface hyaluronidase, internalization of intermediate-size HA, and complete degradation into monosaccharides in lysosomes. Despite considerable research, the identity of the hyaluronidase responsible for the initial HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(185 citation statements)
references
References 45 publications
(54 reference statements)
4
162
0
3
Order By: Relevance
“…No changes in Hyal2 expression occurred after H-I, but there was a significant decrease in expression of Hyal1, which generates HAf oligomers (18). In contrast, expression of Tmem2, a recently described membrane-associated hyaluronidase (20), was significantly elevated after H-I.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…No changes in Hyal2 expression occurred after H-I, but there was a significant decrease in expression of Hyal1, which generates HAf oligomers (18). In contrast, expression of Tmem2, a recently described membrane-associated hyaluronidase (20), was significantly elevated after H-I.…”
Section: Introductionmentioning
confidence: 68%
“…We did not detect PH20 expression in normal or injured neonatal brain, which may suggest that PH20 expression is maturation dependent or transient. In response to neonatal WMI, we observed decreased expression of Hyal1, a hyaluronidase involved in secretion of small-sized HAf from endocytosed HA (18) and increased Tmem2, a recently identified hyaluronidase that generates intermediate-sized HAf (20). This prompted us to explore the hypothesis that intermediate-sized HAf block OPC maturation.…”
Section: Foxo3 Expression Is Markedly Increased In Oligodendroglia Inmentioning
confidence: 98%
“…The levels of HA secreted by colon cancer cells were also not significantly affected by the alteration of HAases expression. The abnormal accumulation of HA in tumor microenvironment is induced by a complex system, including HA synthases, hyaluronidases, transmembrane protein 2, and reactive oxygen and nitrogen species . Knockdown or overexpression of one single HAase may be not enough to influence the HA content.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the cell migration-inducing hyaluronan-binding protein (CEMIP), also known as KIAA1199, which is a secretory protein that has HA-binding and -degrading activities (Yoshida et al, 2013). More recently, transmembrane protein 2 (TMEM2) has been identified as a novel cell surface hyaluronidase (Yamamoto et al, 2017). TMEM2 is a type II transmembrane protein and its hyaluronidase activity resides in its extracellular domain.…”
Section: Hyaluronanmentioning
confidence: 99%
“…With regards to hyaluronidases in the brain, mRNA for HYAL3 was detected in brain tissue via Northern blot analysis (Csoka et al, 1999), and HYAL2 expression was recently revealed in endothelial cells of blood vessels in the brain and in ciliated epithelial cells of the choroid plexus using immunohistochemistry (Chowdhury et al, 2016). In addition, transcripts of both TMEM2 and CEMIP are present in adult mouse brain (Yamamoto et al, 2017). …”
Section: Hyaluronanmentioning
confidence: 99%